Analisis Yuridis Terhadap Sanksi Tindak Pidana Korupsi Di Indonesia Dan Singapura - Siti Nurjanah; Hebrina Antika (Journal of Judicial Review, 2015)
Corruption is derived from the word corruptio or corruptus. Corruption always get more attention than the other crimes in various parts of the world. Indonesian regulations governing the eradication of corruption regulated in Law Number 20 Year 2001 on Corruption. Singapore is one of the countries close to Indonesia. Corruption in Singapore are set in the Prevention of Corruption Act.The purpose of this study was to analyze the criminal sanctions against acts of corruption in Indonesia and Singapore in the review of Law No. 20 of 2001 and the Prevention of Corruption Act.This research was based on normative law and using comparative law on the appication. The data that had been used was primary data and secondary data, those data then will be proceed and been analyzed, qualitative analysis will be used on the data grouping suitabling with the aspect that will be research. Then, the conclusion that related to this studies wil be explained descriptively.Based on the results of the study, it was found that Law No. 20 of 2001 has not been effective in providing criminal sanctions against acts of corruption in Indonesia. It is marked with are still many cases of corruption in Indonesia. While in Singapore, the rules governing the eradication of corruption is considered effective. There are some similarities between the two regulations is that both have set about eradicating corruption. The difference is the agency against corruption in Indonesia is still in control by keeping the parties.